PELATIHAN PENINGKATAN PEMBELAJARAN ONLINE DI MASA PANDEMI COVID-19 PADA GURU SEKOLAH DASAR - Jajang Bayu Kelana; Duhita Savira Wardani (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The Covid-19 pandemic has had a large enough impact, not being excluded from learning in elementary schools. As the spearhead in designing and implementing the learning process, teachers have an important role. The learning process carried out by teachers during the Covid-19 pandemic is certainly different, learning that was previously carried out face-to-face is converted into online learning. Teachers are encouraged to be technology literate and master various online learning media. The purpose of this service is to provide training to elementary school teachers to improve their understanding of online learning during the Covid-19 pandemic. The method used is training using lectures and questions and answers. Community service provides benefits for elementary school teachers in developing their abilities, especially in online learning during the Covid-19 pandemic.